Analisis Pemodelan Numerik Redaman Breakwater Tenggelam Tipe Berlubang dan Tidak Berlubang Menggunakan Sigerd - Lukitawati, Annika; Zakaria, Ahmad; Tugiono, Subuh; Winarno, Dwijoko (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Continuous waves crashing into the coastal area can cause abrasion on the coast and damage facilities and settlements in the area. Therefore, a coastal protection building is needed to reduce wave energy before arriving at the beach such as a breakwater. To design a breakwater it is necessary to pay attention to wave deformation, one of which is wave diffraction. Where the wave when obstructed by an obstacle will bend around the end of the obstacle and enter the protected area behind it. The complex phenomena of nature are described in terms of equations, but they are difficult to solve analytically. So in this study solved numerically with the help of a computer with 2D wave simulation software based on the principle of the hyperbolic equation propagation model. Then get the results in the form of diffraction coefficient values that are close to the results obtained in the physical model research that has been carried out. Changes in wave height occur after passing through the breakwater which indicates a change in energy from before and after passing through the breakwater.